‘Illegal labour practices, trafficking and exploitation’: an introduction to the special issue - Lloyd, Anthony (Trends in organized crime, 2020)
This is an introduction to the articles submitted to the special issue of Trends in Organized Crime on ‘Illegal Labour Practices, Trafficking and Exploitation’. The aim of the special issue is to draw together empirical research findings and theoretical accounts on the wider context to illegal labour and exploitation that has implications for identification, detection, prevention and regulation.